2018
DOI: 10.31579/2641-0427/005
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of D-dimer Level Fluctuation in Patients after the Cemented and Cementless Total Hip and Total Knee Replacement

Abstract: The number of total hip and total knee replacement procedures performed worldwide has tended to surge in recent years, due to the combination of such factors as the increased life expectancy, improved quality of life, advances in medical technology as well as pre-operative and post-operative patient management. Numerous studies confirm that patients undergoing major orthopedics procedures involving lower extremities, for instance total hip and total knee replacement, constitute the highest risk group for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…There was a trough on the third day after surgery. Bytniewski et al 27 investigated the dynamics of D-dimer level after the cemented and cementless total hip and total knee replacement, and found a similar tendency, which was consistent with our research. The reasons for the elevation of D-dimer after surgery may be due to surgical trauma, anaesthesia interference, intraoperative blood loss and blood transfusion, the activation of coagulation system by implants, and the participation of various inflammatory mediators in the body to promote coagulation under stress.…”
Section: Discussionsupporting
confidence: 92%
“…There was a trough on the third day after surgery. Bytniewski et al 27 investigated the dynamics of D-dimer level after the cemented and cementless total hip and total knee replacement, and found a similar tendency, which was consistent with our research. The reasons for the elevation of D-dimer after surgery may be due to surgical trauma, anaesthesia interference, intraoperative blood loss and blood transfusion, the activation of coagulation system by implants, and the participation of various inflammatory mediators in the body to promote coagulation under stress.…”
Section: Discussionsupporting
confidence: 92%
“…Reducing unnecessary blood tests can also reduce costs and prevent wasting resources [22]. Previous studies to date have demonstrated that serum D-dimer testing up to 10 days after a total knee replacement should not be used as a diagnostic test [9,10]. Our study suggests that D-dimer testing is a poor choice of investigation for VTE for up to 28 days after surgery and should be avoided and replaced with more accurate radiological investigations.…”
Section: Discussionmentioning
confidence: 82%
“…Studies have demonstrated that after TKR, serum D-dimer levels remain elevated from day 0 to day 10 post-operatively [9,10], with no significant difference in D-dimer level between patients with or without a DVT from day 0 to day 10 following surgery [3,9,10]. Bytniewski et al [10] found that higher levels of serum D-dimers in the post-operative period of up to 10 days were not related to increased risk of VTE. Due to its low specificity in this period, the use of serum D-dimer within the first 10 days following TKR is not recommended as a screening tool for VTE [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to Ribera et al, the level of synovial D-dimer is higher than normal in foal infectious joint disease [34]. The results of the study done by Bytniewski et al show that the level of D-Dimer in patients with early postoperative TJA changes faster than that of ESR and CRP, and can rise rapidly and return to normal level in a short time [36]. Subsequently, the diagnostic value of D-dimer in patients with PJI began to be valued by joint surgeons.…”
Section: Discussionmentioning
confidence: 97%